SEMIOTIKA KATO NAN AMPEK REMAJA DUSUN PADANG GAJAH MATI JORONG SAGO NAGARI MANGGOPOH KABUPATEN AGAM SUMATERA BARAT - Silvia Rahmadani; Oktri Permata Lani (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The main problem in this journal is that the use of kato nan ampek has begun to rarely applied by teenagers, while as Minangkabau people, kato nan ampek must be used ineverday life. The meaming of kato nan ampek is a rule or noms that goverm a person when speaking politely when communicating. At this time teeanagers are influenced by social media and cannot use sosial media wisely so they do not get knowlendge about kato nan ampek. This research was conducted in dusun Padang Gajah Mati , Jorong Sago nagari Manggopoh using qualitative research. The data collection techniqeus used were observation, interviews, and dokumentation. The results daily lives because teenager are already influenced by outside culture and are not wise in using social media.